Assessment of the quality of patient‐orientated internet information on surgery for ulcerative colitis. (June 2015) - Sacchi, M.; Yeung, T. M.; Spinelli, A.; Mortensen, N. J.
Abstract Aim This study examines the quality of websites providing information on ulcerative colitis, including treatment options and surgery. Method Two search engines (Google and Yahoo) and the search term 'surgery for ulcerative colitis' were used. The first 50 sites obtained with each search engine were assessed. Sites were evaluated for content and scored using the DISCERN instrument, which evaluates the quality of health information on treatment choices. Results One hundred sites were examined, of which 14 were duplicates. Of the remainder, 58 provided patient‐orientated information for adults and one site provided information for surgery in children. The other 27 sites included six scientific articles, three blogs, three links, six resources for clinicians, five fora, two video links and two dead links. Of the 58 websites that provided patient information for adults, only 26 (44.8%) had been updated within the last 2 years. Only 13/58 (22.4%) were affiliated to hospitals and clinics. Most sites (38/58, 65.5%) were associated with private companies with commercial interests. Although most websites contained information on symptoms and treatment options for ulcerative colitis, 37 (63.8%) did not describe any of the risks of surgery. Overall, only seven (12.1%) websites were identified as being 'good' or 'excellent' using the DISCERN criteria. Conclusion The quality of patient information on surgery for ulcerative colitis is highly variable. There is potential for internet provision of valuable information and clinicians should guide patients with to access high‐quality websites.